Unpredictable Nature of Tolvaptan in Treatment of Hypervolemic Hyponatremia: Case Review on Role of Vaptans - Ishan Malhotra; Shilpa Gopinath; Kalyana C. Janga; Sheldon Greenberg; Shree K. Sharma; Regina Tarkovsky (Case Reports in Endocrinology)
Hyponatremia is one of the most commonly encountered electrolyte abnormalities occurring in up to 22% of hospitalized patients. Hyponatremia usually reflects excess water retention relative to sodium rather than sodium deficiency. Volume status and serum osmolality are essential to determine etiology. Treatment depends on several factors, including the cause, overall volume status of the patient, severity of hyponatremic symptoms, and duration of hyponatremia at presentation. Vasopressin antagonists like tolvaptan seem promising for the treatment of euvolemic and hypervolemic hyponatremia in heart failure. Low sodium concentrations cause cerebral edema, but the overly rapid sodium correction can also lead to iatrogenic cerebral osmotic demyelination syndrome. Demyelination may occur days after sodium correction or initial neurologic recovery from hyponatremia. The following case report analyzes the role of vasopressin antagonists in the treatment of hyponatremia and the need for daily dosing of tolvaptan and the monitoring of serum sodium levels to avoid rapid overcorrection which can result in osmotic demyelination syndrome (ODS).